2001
DOI: 10.1007/s004170100353
|View full text |Cite
|
Sign up to set email alerts
|

Adenocarcinoma of the nonpigmented ciliary epithelium: report of two cases with immunohistochemical findings

Abstract: Patient 1 was a 39-year-old man who presented with a pigmented mass behind the iris and secondary exudative retinal detachment. The eye also developed neovascular glaucoma. Patient 2 was a 44-year-old woman with a ciliary body mass but without symptoms. Both of these tumors were classified histologically as low-grade adenocarcinomas of the NPCE from specimens successfully removed by iridocyclectomy. Immunohistochemical findings confirmed the origin of the tumor cells; however, some changes in the immunoreactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…AE1 specifically recognizes the keratins in the acidic subfamily and AE3 recognizes the keratins in the basic subfamily. AE3 has been found in both nonpigmented ciliary epithelial tumor cells and non‐neoplastic cells, whereas AE1 was only expressed in tumor cells 51 . This study found the adenocarcinomas to have the highest expression of AE1/AE3 with less expression in the adenomas.…”
Section: Discussionmentioning
confidence: 60%
“…AE1 specifically recognizes the keratins in the acidic subfamily and AE3 recognizes the keratins in the basic subfamily. AE3 has been found in both nonpigmented ciliary epithelial tumor cells and non‐neoplastic cells, whereas AE1 was only expressed in tumor cells 51 . This study found the adenocarcinomas to have the highest expression of AE1/AE3 with less expression in the adenomas.…”
Section: Discussionmentioning
confidence: 60%
“…2.2.1. Ocular tumors-NVG has been reported in association with prior to treatment in ring melanoma of the anterior uvea (Allaire et al 1997), adenocarcinoma of the nonpigmented ciliary epithelium (Terasaki et al 2001), medulloepithelioma (Singh et al 2001), circumscribed choroidal hemangioma (Shields et al 2001a), metastatic cutaneous melanoma to the vitreous (Gunduz et al 1998), retinoblastoma (De Potter 2002, and metastatic malignant lymphoma (Matsui et al 2005).…”
Section: Uncommon Ocular Causes Of Nvgmentioning
confidence: 99%
“…In general, adenoma of the RPE is negative for HMB-45,15 in contrast to malignant melanoma. However, there is a single report of adenoma of the RPE that was positive for HMB-45 11.…”
Section: Discussionmentioning
confidence: 94%